SUCH MOTHER, SUCH SPIDERLINGS: OFFSPRING OF URUGUAYAN WOLF SPIDERS (ARANEAE: LYCOSIDAE) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
The current study explores information available about number of egg sacs and spiderlings in 14 lycosid species from Uruguay. We found a positive relationship between female body size and progeny, in agreement with hypotheses that propose that larger body size favors fecundity in spiders.
Keywords: Lycosids; spiderlings; number of egg sacs; body size